Impact of SERVQUAL Dimensions on Customer Satisfaction with Ambulance Service Call Center Questioning System: Case of Qatar - Zied Gherissi (18505311) (2024)
Background To achieve the Qatar National Vision 2030, the healthcare sector in Qatar seeks to adopt a patient-centered approach. This promotes the general public engagement to participate in decision-making processes. To be involved and proactive, customers should be motivated and satisfied. Therefore, Qatar’s Ambulance Service Call Center2 was evaluated as part of a quality improvement study by determining its 999 caller`s level of satisfaction depending on their gender and highest education qualification. Methods An online survey in three different languages was developed and tested using the SERVQUAL (Service Quality) model3 and distributed to Qatar’s 999 caller`s to assess their satisfaction level with service delivery. Results A total of 265 participants were recruited (Male=140; Female=125). Their mean satisfaction score was 5.98 SD 0.469 for men and 5.96 SD=0.432 for women, out of a maximum score of 7. Pearson Correlation Test showed a strong positive correlation between the SERVQUAL dimensions and customer satisfaction, and between public awareness and customer satisfaction (Table 1). There were no statistically significant differences in male's and female`s perceptions of customer satisfaction, however the One-Way ANOVA test followed by a Tuckey test revealed a statistically significant satisfaction difference between those with a high school and graduate qualification and between those with high school and doctorate degrees (Table 2). Conclusion This is the first program that discussed customer satisfaction with the scripted questioning system (Medical Priority Dispatch System - MPDS). This study may have implications for other users of this system. It is hoped to encourage leaders and researchers to investigate this subject from different perspectives and use different service quality measurement tools. The Ambulance Service Training Department will focus on some areas showing weakness in the research or significant relationships between dimensions and customer satisfaction.